What Is the Value of (My and My Family's) Good Health? - de Mello, Luiz; Tiongson, Erwin R. (2012)
This paper uses several waves of the General Social Survey (GSS) including data for up to about 32,000 individuals to estimate the effect of a variety of health conditions on happiness. We show that healthy people are in general happier than individuals with poor health, controlling for a number of personal and household characteristics. On the basis of the regression results, we computed the monetary value of good health, suggesting that relatively large sums of money would be required to compensate individuals for the loss in happiness associated with poor health. Finally, we show that people become unhappy when the health status of their loved ones deteriorates. In particular, the compensating value associated with a spouse's poor health can be very large, thus pointing to some altruism in the relationship between health status and happiness.